Characterizing integration challenges in mission engineering to form solution strategies. Issue 4 (10th May 2022) - Hernandez, Alejandro S.; Pollman, Anthony G.
Abstract: This paper presents a systematic approach to characterize integration challenges when implementing mission engineering and discusses some specific techniques to address these issues. With the introduction of mission engineering in the DOD science and technology lexicon, integration assumes a new dimension beyond the system product level. First, the authors offer a more precise definition of integration that focuses on incorporating a new technology or military capability into an existing organization's infrastructure. Using a collection of system integration literature and a set of examples, the authors define major problem areas regarding integration. Analyses of these issues present opportunities to identify specific methods to avoid or mitigate them. The resultant process is a foundation for mission engineering practitioners to plan successful integration of a new system. Acceptance of these procedures in the mission engineering community may lead to inclusion as standard practices in the DOD Mission Engineering Guide.